Defamilisation measures and women's labour force participation – a comparative study of twelve countries. Issue 1 (2nd January 2017) - Chau, Ruby C.M.; Yu, Sam W.K.; Foster, Liam; Lau, Maggie K.W.
Abstract : This paper examines the relevance of two interpretations of defamilisation ("freedom of the family" and "freedom of women from the family") to the search for effective measures for strengthening women's participation in the paid labour market. Based on these two interpretations, two types of defamilisation measures (care-focused and women's economic) are identified. Two defamilisation indices are developed respectively covering twelve countries. The importance of the two types of defamilisation measures in assisting women to access employment are discussed from two angles. The input angle refers to the extent to which countries are committed to the provision of these defamilisation measures. The output angle is about the relationship between these defamilisation measures and the degree of women's participation in the paid labour market. Through conducting these analytical tasks, this paper also contributes to the examination of the relationship between types of welfare regimes and the provision of defamilisation measures.